Ğihād al-Nafs: An Inquiry into Striving and Spirituality in Dialogue with Western Psychology - Colonello, Paola (Al-Jadwa: Jurnal Studi Islam, 2025)
The research problem stems from the frequent mischaracterization of ğihād al-nafs as a harsh battle “against” the self, waged to suppress the lower nafs. By framing inner striving as its object of inquiry, the study reframes Muslim spiritual endeavour as a practice aimed at cultivating mastery over self-sabotaging instincts, fostering inner coherence, and, above all, restoring order (amr) within the domain of consciousness. As the results suggest, the discrimination of vices and the integration of virtues are not mutually exclusive, but interdependent dynamics that enable the inclusion of what supports the evolution of consciousness. Adopting a literature-based approach within a hermeneutic epistemological framework, the essay draws upon classical Islamic sources while engaging with insights emerging from Western psychology, concluding that ğihād al-nafs is a form of struggle “in favour” of the soul, prompting the correction of inner imperfections, alongside the actualization of latent virtues and potential. As a distinctive contribution, the paper demonstrates how contemporary psychological understandings of striving and spirituality may illuminate the motivational logic underpinning Muslim inner struggle, revealing it as a process of optimization: a way of attuning to the deepest expression of humanity, which precedes and enables spiritual proximity to the Divine.